Executive Committee Minutes 2021-02-25 - Academic Senate:::::::::
Approval of Agenda – items added. Approved. Minutes of 2/11/2021 – Approved. Chair Report. President Report. Provost Report. Statewide Senator Report. From EPC: Revision to BA in Philosophy – Approved for Senate consent calendar. Vice President of Administration and Finance Report. Associated Students Report. From FSAC: AFS/PDS Statement on Teaching Sensitive Materials – Approved for endorsement on Senate Agenda. From SDS: Syllabus Checklist for Diversity/Inclusivity – Approved for endorsement on Senate agenda. Academic Senate Resolution on Administrative Encroachment into Curricular Matters – Approved for Senate Agenda. From APARC: Letter to Ex Com regarding Syllabus Policy – Approved for Senate Agenda. Senate Agenda Approved.